Hybrid quantum system based on rare earth doped crystals - Probst, Sebastian (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2016)
Hybrid quantum circuits interfacing rare earth spin ensembles with microwave resonators are a promising approach for application as coherent quantum memory and frequency converter. In this thesis, hybrid circuits based on Er and Nd ions doped into Y?SiO? and YAlO? crystals are investigated by optical and on-chip microwave spectroscopy. Coherent strong coupling between the microwave resonator and spin ensemble as well as a multimode memory for weak coherent microwave pulses are demonstrated.